2014
DOI: 10.1002/em.21854
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dose–response analysis of ethyl methanesulfonate genotoxicity in adult gpt‐delta transgenic mice

Abstract: The assumption that mutagens have linear dose-responses recently has been challenged. In particular, ethyl methanesulfonate (EMS), a DNA-reactive mutagen and carcinogen, exhibited sublinear or thresholded dose-responses for LacZ mutation in transgenic Muta™Mouse and for micronucleus (MN) frequency in CD1 mice (Gocke E and Müller L [2009]: Mutat Res 678:101-107). In order to explore variables in establishing genotoxicity dose-responses, we characterized the genotoxicity of EMS using gene mutation assays anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 52 publications
0
43
1
Order By: Relevance
“…More recently, Cao et al [113] have conducted experiments in which male gpt-delta transgenic mice were treated daily for 28 days with 5-100 mg/kg EMS, and measurements were made on: (i) gpt mutant frequencies in liver, lung, bone marrow, kidney, small intestine, and spleen; and (ii) Pig-a mutant frequencies in peripheral blood reticulocytes (RETs) and total red blood cells. MN induction also was measured in peripheral blood RETs.…”
Section: Appendix 2 Ems/viracept ® Case Study: Example Of a Successfmentioning
confidence: 99%
“…More recently, Cao et al [113] have conducted experiments in which male gpt-delta transgenic mice were treated daily for 28 days with 5-100 mg/kg EMS, and measurements were made on: (i) gpt mutant frequencies in liver, lung, bone marrow, kidney, small intestine, and spleen; and (ii) Pig-a mutant frequencies in peripheral blood reticulocytes (RETs) and total red blood cells. MN induction also was measured in peripheral blood RETs.…”
Section: Appendix 2 Ems/viracept ® Case Study: Example Of a Successfmentioning
confidence: 99%
“…For alkylating agents, representative studies include three in vitro [56-58] and three in vivo [2, 3, 138] low-dose dose-response genotoxic datasets (an example is presented in Figure 4). The genotoxic chemicals used in these studies included direct-acting, monofunctional ethylmethanesulfonate (EMS), MMS, ethylnitrosourea (ENU), and MNU, although not all of the studies used all four chemicals.…”
Section: Alkylating Agentsmentioning
confidence: 99%
“…The data clearly demonstrated an increasing level of hydroxyethylvaline hemoglobin adducts corresponding with increasing administered dose of EMS, but with no increase in corresponding MN induced until the administered dose exceeded the 80 mg/kg bw/day dose in mouse. Mutational in vivo dose-response with EMS was also recently investigated in adult gpt-delta transgenic mice within different tissues at the gpt transgene and at the Pig-a endogenous gene [2]. In the study, measured mutation NOGELs were identified at below 13 mg/kg/day and the lowest calculated PoD value, BMDL 10 , of 0.038 mg/kg/day was found in the lung of gpt-delta mice.…”
Section: Alkylating Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This led researchers to 48 question the reliability of the general assumption of dose-49 response linearity at low doses for numerous genotoxicants with 50 diverse modes of action (MoA). In this context, the term MoA can 51 be defined as the sequence of key events and processes involved in 52 the interaction of an agent with DNA or other cellular target 53 structures that result in specific DNA damage [10]. 54 Non-linear dose-responses have been reported for low doses of 55 compounds with diverse MoA such as aneugens topoisomerase 56 inhibitors, alkylating agents and oxidants by evaluating different 57 genotoxic endpoints (e.g.…”
mentioning
confidence: 99%